Media Flashcard untuk Optimalisasi Hasil Belajar Siswa di Sekolah Dasar - Roni Rodiyana; Wina Dwi Puspitasari; Ari Yanto (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2022)
ABSTRAKIn their intellectual development, elementary school students are at the concrete thinking stage. Everything that the teacher conveys must be realistic and can develop all the abilities that exist in children. There needs to be a solution, namely by using flashcard image media. In particular, graphics also function to attract attention, clarify presentation of ideas, illustrate or decorate facts that would be quickly forgotten or ignored if not graphically. Flashcards are very suitable for practicing spontaneous speaking skills by using certain sentence patterns so that learning objectives will be achieved optimally, especially in student learning outcomes.